Message from Guest of Honor (Trinity Journal of Management, IT & Media (TJMITM), 2022)
It gives me great pleasure to know that Trinity Institute of Professional Studies (TIPS), Dwarka is organizing TIPSCON2022, 11th National Conference on Resilience & Reinvention: A path for change in Management, IT, Media and Law on 22-Jul-22.It is really worth noting that this is being attended by Academicians, Research Scholars, Students and Corporate Executives - all of whom can not only benefit from this conference but also contribute by proper involvement in this inevitable change in future too.We are all witness to the speed of change when it is inevitable, by the effect COVID had on our lives. The change got initiated within a couple of days and the leadership / management skills were put on a test never seen before. Business models changed overnight and within a short span of time, leadership of all organizations were working frantically on both soft and hard factors - keeping relationship with customers healthy as well as motivating employees and at the same time establishing processes, which were never tried before. In this crisis situation, IT played an important role and robust systems were put in place re-inventing at lightening speeds. Virtual offices with appropriate automation, security, on cloud and network were setup overnight and physical meetings turned to virtual meetings almost on an immediate basis. This re-invention, though initiated by the onset of COVID, found its way quickly into various aspects of life and paved the path for implementation even on the domestic front with families connecting like never before. Along with the set-up on these virtual offices, focus has also been given to real time backup, disaster recovery, stronger network connectivity, remote error resolutions and risk management.With changes and disruptions taking place across all industries, the media and entertainment is no exception and is being challenged by newer models coming up. The mainstream media like News Houses are being challenged by News available on platforms like YouTube and entertainment mediums like the Film Industry are being challenged by local groups coming up with storylines and putting them up on the various online platforms like YouTube, Instagram, Facebook and the likes. Unless the traditional media houses catch up on the waves of change and ride on them by adopting resilience and re-invention while adopting the various IT tools available, being exploited by the non-traditional businesses, they may be left far behind.The same is true for the Law and though the traditional Legal System in India may not be affected directly right now, we cannot ignore the fact that the world is getting closer by the day and regional and country boundaries are shrinking. It’s very easy to cross boundaries of countries and even continents with their own unique legal and cultural systems - with intermingling of both across societies and countries. In this situation, having an understanding of Law of multiple countries will give a definite advantage and will equip anyone with knowledge on how to handle the situation - especially if it affects multiple countries, like criminals crossing boundaries to save themselves. If they can adopt technology to escape the Law, it becomes imperative for the Law of these countries to adopt latest processes and technologies to stay one step ahead of such criminals.The integration and re-invention of the 4 pillars being discussed in this conference – Management, IT, Media and Law will definitely help in establishing a system which can propel not only the people who have adopted them, but also the respective Industry and Country which adopt these. Once again, I congratulate Trinity Institute of Professional Studies (TIPS) for organizing this conference and my best wishes for the same.